Serum Prealbumin: a potential predictor of Right Ventricular Dysfunction in patients receiving programmed hemodialysis - Gok,Murat (2022)
SUMMARY OBJECTIVE: Prealbumin has been a reliable marker to predict protein energy malnutrition and hypercatabolic state. In this analysis, we particularly aimed to investigate the potential association between serum prealbumin levels and right ventricular dysfunction in patients receiving programmed hemodialysis. METHODS: A total of 57 subjects were included in the analysis. The subjects were then categorized into two groups: right ventricular dysfunction (n=18) and non-right ventricular dysfunction (n=39) groups. In all patients, detailed transthoracic echocardiography (following hemodialysis) were performed along with the evaluation of complete blood count, routine biochemistry parameters, and, in particular, serum prealbumin levels. RESULTS: Mortality rate at 3 years was found to be significantly higher in the right ventricular dysfunction group (p=0.042). Serum prealbumin levels were also significantly lower in the right ventricular dysfunction group compared with the non-right ventricular dysfunction group (23.83±8.50 mg/dL versus 31.38±6.81 mg/dL, p=0.001). In the receiver operating characteristics curve analysis, a prealbumin cutoff value of <28.5 mg/dL was found to predict right ventricular dysfunction, with a sensitivity of 67% and a specificity of 62% (area under the curve: 0.744). In the correlation analysis, a moderate yet significant positive correlation was demonstrated between serum prealbumin and tricuspid annular plane systolic excursion (r=0.365, p=0.005). CONCLUSION: This study suggests that low serum prealbumin might serve as a potential predictor of right ventricular dysfunction (and its clinical consequences) in patients receiving programmed hemodialysis.